SWEDISH SUBURBS AS HETEROTOPIAS: TOWARDS A MULTICULTURAL LITERATURE OF PLACES - Gendolavigna, Luca (PEOPLE: International Journal of Social Sciences, 2021)
Urban literary studies have become an important issue in contemporary multicultural Sweden, especially after the 70s, when the public housing project Miljonprogram (“Million Programme”) was completed (1974). Nowadays, these areas are partly regarded as a political failure since they have become places of social and even racial segregation. A central cultural consequence of multiculturalism in Sweden is the so-called Invandrarlitteratur (“immigrants’ literature”), mainly represented by second-generation authors. In this article, I will try to provide a concise but exhaustive understanding of how this kind of literature can reshape the Miljonprogram areas and define what Sweden is today. The aim is to show how these suburban spaces, through a chosen collection of three works, are narrated by immigrant authors not as sites, i.e. spaces as such, but rather as places, i.e. spaces whose meaning is provided by the (literary) subjectivities who live and act therein (Prieto 2013). Using the concept of heterotopia (Foucault 1986) and its defining criteria, I will investigate how these works perform a total reassertion of space, emphasizing the space described as rhizomatic (Deleuze & Guattari 2011) peripheries, i.e. the result of a sensitive relationship between self and space. This investigation is designed to reflect on how the perception of suburbs has changed from first to second-generation immigrant writers and it hopes to open a new research line in which stigmatizing dystopias can be replaced by heterotopias.